Villous Adenoma Arising in the Urethra of a Female with Bladder Augmentation History: A Case Report and Review of the Literature - Hale DEMIR; Selçuk CIN; Sinharib CITGEZ; Nesrin UYGUN (Federation of Turkish Pathology Societies, 2021)
Villous adenomas (VAs) in the female urethra are rare with only seven cases in the English literature to our knowledge. In patients with bladder augmentation cystoplasty, the neoplasia development risk increases and most of these develop in the neobladder or anastomosis line. Only two cases of VA developing from the native bladder mucosa have been reported. Physical examination of a 76-year-old female who had a history of augmentation cystoplasty revealed a caruncula-like structure protruding from the urethral meatus. The urinary USG showed that the lesion had no relation with the bladder. The lesion was excised. Microscopically, it consisted of villous structures covered with pseudostratified intestinal type epithelium. Low-grade dysplasia was present in the epithelium but high-grade dysplasia or in-situ/invasive carcinoma was not observed. Immunohistochemical study showed positivity for CK7, CK20, EMA, CEA and CDX2. The case was reported as VA of the urethra. We presented the first VA case arising in the urethra of a female patient with intestinal bladder augmentation. Excision is curative for pure VAs. Transformation to carcinoma or recurrence has not been reported. However, in one third of the cases, a malignant tumor may accompany the lesion. Therefore, all excision material should be examined carefully. Routine endoscopic follow-up should be performed in cases with bladder augmentation.